Spatial-Temporal Analysis of Land Cover Changes in Southwest Maluku Regency, Maluku Provinc - Rakuasa, Heinrich; Sihasale, Daniel Anthoni (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2022)
The development of built-up land in Southwest Maluku Regency (MBD) has been steadily increasing each year, as evidenced by the analysis of land cover changes in 2012, 2017, and 2022. Understanding the development and changes in land cover is crucial for predicting future land cover patterns and for preventing or mitigating potential negative impacts. This study aims to analyze the land cover changes in the Southwest Maluku Regency. The analysis of land cover changes in Southwest Maluku Regency was conducted using Landsat 4-5 TM, Landsat 8 OLI, and SPOT 7 imagery, which involved pre-processing and land cover classification processes based on the SNI 7645:2010 standard. The results of the study indicate that built-up land in MBD is generally concentrated in the Moa Lakor District, Letti Island District, and Terselatan Islands District. Tiakur Village has experienced the most rapid development of built-up land in MBD, as it is the capital of the Southwest Maluku Regency.